Pengaruh Model Pembelajaran Problem Based Learning Dan Kecerdasan Linguistik Terhadap Kemampuan Menyusun Laporan Hasil Observasi Pada Sisw - Padlurrahman, Padlurrahman (Universitas Hamzanwadi, 2023)
This study aims to determine the influence of the Problem-Based Learning model and linguistic intelligence on the ability to compile observation reports for X graders of MA Muallimin NWDI Kelayu. This research is classified as quantitative research using experimental methods with a treatment design by level 2x2. The subjects of this study consisted of class XA students as an experimental class and class XB students as a control class. Linguistic intelligence data were collected using questionnaires, and data on the ability to compile reports of observations were collected using tests. Furthermore, the collected data was analyzed using ANAVA with SPSS-assisted version 26.The results show that 1) the Problem-Based Learning (PBL) model had a significant effect on the ability to compile observation reports where 0.00 < 0.05 with an influence of 80.8%; 2) linguistic intelligence has a significant effect on the ability to compile observation reports where 0.00 < 0.05 with an influence of 70.2%; 3) there is no interaction between the Problem-Based Learning (PBL) model and linguistic intelligence on the ability to compile observation reports with 0.109 > 0.05. Keywords: Problem-Based Learning, Linguistic Intelligence, Observation Report